Eu3+-doped highly thermal-stable barium yttrium aluminate as a red-emitting phosphor for UV based white LED. (April 2019) - Gao, Zhiwen; Sun, Pengfei; Zhong, Yifan; Yu, Ruijin; Deng, Bin
Highlights: Ba2 YAlO5 :Eu 3+ red-emitting phosphor was prepared. The excitation spectrum matches well with near-UV LED chips. The phosphor shows excellent thermal-stability. The red-emitting LED was fabricated based on the InGaN chip. Abstract: A series of novel Eu 3+ activated aluminate Ba2 Y1− x Eu x AlO5 ( x = 0.02–0.40) red-emitting phosphors were synthesized through a high-temperature solid-state route at 1380 °C. The phosphors were well crystallized in the space group P 21 /c (No. 14). Their photoluminescence emission (PL) and excitation (PLE) spectra were investigated. The results indicate that the Ba2 YAlO5 :Eu 3+ phosphor can be excited effectively under 394 nm irradiation, which is suitable for UV LED chip. The obtained Ba2 YAlO5 :Eu 3+ phosphor shows four peaks, corresponding to the 5 D0 – 7 FJ (J = 0, 1, 2, 3 and 4) transitions of Eu 3+ upon 394 nm excitation. The optimal doping concentration of Eu 3+ in Ba2 YAlO5 : x Eu 3+ was determined at 30 mol%. By temperature dependent emission spectra, the quenching temperature for Ba2 YAlO5 :0.30Eu 3+ was found to be over 500 K. And the CIE chromaticity coordinates of Ba2 YAlO5 :0.30Eu 3+ are very close to the National Television System Committee (NTSC) standard red.